Correlation Between Magnetic Resonance Imaging and Histopathology of Primary Brain Gliomas and Metastasis - Afnan W. Al Esawi; Iftikhar Altemimi; Riyadh W. Al Esawi; Kaswer Musa Alturaihi; Alla Salah (Open Journal of Physicians and Surgeons, 2025)
Introduction: Glial cells constitute 90% of the central nervous system, playing a vital role in neuronal support. Glial tumors vary from benign (WHO grade 1) to highly malignant (WHO grade 4), with glioblastomas being the most aggressive. The 2021 WHO classification includes diffuse gliomas, such as astrocytomas and oligodendrogliomas. Risk factors include ionizing radiation, while genetic predisposition accounts for less than 5% of cases. MRI with gadolinium is the primary imaging tool, with advanced techniques like DWI, PWI, and MRS aiding in tumor characterization. The aim of the study: To evaluate the relationship between MRI features and histopathological diagnosis of primary brain gliomas, with an emphasis on the ability of MRI to distinguish between glioma grades, predict tumor aggressiveness using conventional MRI, and differentiate gliomas from metastasis and other brain lesions. Subjects and Methods: A cross-sectional study was conducted on 80 adult patients diagnosed at Al-Furat AL- Awsat Oncology Center between January 2022 and January 2024. Preoperative MRI and postoperative histopathological samples were analyzed to establish the final diagnosis. Results: Primary brain tumors predominantly affect adult individuals ranging from (20-74) years, with a higher prevalence in males (61.25%). Glioblastoma is the most common glial tumor represent (43.7%), supratentorial region most common site (92.5%). A significant gap exists in IDH mutation testing (64.1% untested), which is crucial for prognosis and treatment. Most tumors exhibit irregular outlines (75.1%) and lack diffusion restriction (76.2%), with ring enhancement (38.8%) being the most common contrast pattern. MRI shows moderate accuracy (66.25%) with glioma grading and total accuracy to detect GBM was (77.5%). Conclusion: Glioblastoma was the most common type that occur commonly in male, majority of cases situated in supratentorial region. MRI imaging is essential for the initial diagnosis, and can help in assessing tumor grade and differentiating gliomas from other brain lesions but may struggles in some cases. statistical analysis indicates moderate MRI- histopathological agreement, so histopathology remains the gold standard for diagnosis of glioma. Finally, the integration of clinical correlation, MRI imaging and histopathology is crucial for definitive diagnosis.